Churning and profitability in the U.S. corporate sector - Leila Davis; Joao de Souza (University of Massachusetts, Department of Economics, 2021)
This paper establishes that entry and exit regulate the top half of the profitability distribution in the post-1970 U.S. economy. We, first, document stability in the distribution of total profits earned on tangible, intangible, and financial capital. Whereas a narrower measure of returns on tangible capital, instead, suggests rising dispersion, it fails to capture post-1970 growth in intangible and financial assets. Second, we use quantile decompositions to show that churning - specifically, exit for cause - regulates median and top-end profitability. Thus, the process by which competition drives out unprofitable firms acts to stabilize profit rates in the U.S. economy.
Keywords: B5; L1; 330; Profit rates; competition; entry and exit dynamics